Perception about COVID-19 vaccine among patients at the federal medical centre, Yenagoa, South-South Nigeria - Oriji, Peter Chibuzor; Allagoa, Dennis O.; Obagah, Lukman; Tekenah, Ebiye S. E.; Ohaeri, Onyekachi S.; Atemie, Gordon (International Journal of Research in Medical Sciences, 2021)
Background: The severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) is the causative organism of the coronavirus disease 2019 (COVID-19), which is a respiratory disease that was first identified in December, 2019 in Wuhan, China. Objective was to determine the perception of the COVID-19 among patients at the Federal Medical Centre, Yenagoa, Bayelsa State, Nigeria. Methods: This study was carried out at the Federal Medical Centre, Yenagoa between 4th January and 15th February, 2021. It was a descriptive cross-sectional study. The study population consisted of 1,000 consecutive patients that presented to the various out-patients departments of the hospital. Written informed consent was obtained. The data were collected with a predesigned questionnaire, and were analysed using statistical software (SPSS for windows® version 23, SPSS Inc.; Chicago, USA). Results: Out of 1,000 participants, only a quarter of the participants (24.6%) indicated willingness to take the COVID-19 vaccine when available in Nigeria. About one-tenth of the participants have had loss of sense of taste and smell (11.7%), and think they possibly may have been infected with the COVID-19 (10.8%) in the recent past. Among those that were unwilling to take the COVID-19 vaccine, 14.2%, 9.0% and 7.5% thought that hydroxychloroquine, azithromycin and septrin respectively, are safe alternatives to the vaccine. Conclusions: Although it is known that hypothetical choices may not always reflect real life decision, it is important for policy makers and stakeholders to pay more attention on health education and campaign, targeted at addressing the misconception about COVID-19 vaccine.